Використання технології кінематики в реальному часі (RTK) для розв’язання прикладних задач геодезії - Задемленюк, Антоніна Володимирівна (Національний університет "Львівська політехніка", 2011)
Дисертація присвячена розв’язанню прикладних задач геодезії з використанням сучасних супутникових технологій в режимі реального часу. Визначення координат пункту з точністю 2-3 см в режимі RTK протягом декількох секунд, підтверджено на основі проведених експериментальних досліджень, а застосування сучасного мультичастотного GNSS обладнання спільно з використанням GPRS Internet зв’язку, дає можливість працювати пересувному приймачу користувача від однієї референцної станції на відстані до 200 км. Для розв’язання питання, пов’язаного з переходом від однієї системи координат до іншої в режимі реального часу, запропоновано використання одно етапної процедури трансформування координат для тих польових контролерів, які мають можливість працювати із трансформаційними полями. Ця процедура базується на накладанні на трансформаційне поле (УСК-2000 - СК-42) додатково змодельованих значень різниць координат (ETRS89 - УСК-2000). Диссертация посвящена решению прикладных задач геодезии с использованием современных спутниковых технологий в режиме реального времени. Определение координат пункта с точностью 2-3 см в режиме RTK в течение нескольких секунд, проверено на основе проведеннях исследований, а применение современного мультичастотного GNSS оборудования совместно с использованием GPRS Internet связи, дает возможность работать передвижному приемнику пользователя от одной референцной станции на расстоянии до 200 км. Для решения вопроса, связанного с переходом от одной системы координат к другой в режиме реального времени, предложено использование одноэтапной процедуры трансформации координат для полевых контроллеров, имеющих возможность работать с трансформационными полями. Эта процедура основана на наложении на трансформации поле (УСК-2000 - СК-42) дополнительно смоделированных значений разностей координат (ETRS89 - УСК-2000). The dissertation is devoted to the solution of applied problems of geodesy with the help of current satellite technologies in real-time operation mode. Classical geodesic methods of coordinate estimation are being recently substituted by current satellite systems allowing to perform field surveying several times faster and the necessity of additional office studies disappeared. Thus, for instance, the coordinates of a location with the precision of 2-3 cm can be obtained with the help of Real Time Kinematics (RTK) within several seconds. Only the presence of an active reference center (or the network of such stations) is necessary for the user's multichannel GNSS receiver to obtain the corrections and to precisely estimate the location. In presence of active reference station there is no more necessary to install a base station with the radius of action of about 30 km and the additional difficulties appear for signal transmission to the user's location. Due to the fact that at the time we have initiated our experimental observations no active reference station or network existed, the corrections we received for our mobile receiver, initially came from our base station, and from a permanent SULP station afterwords. The extensive experimental measurements have been performed by modern dual channel GNSS equipment with the help of GPRS mobile Internet connection providers. Basing on the results of our observations, the possibility of RTK technology application is confirmed on the example of L'viv Region. We came to the conclusion that one active reference station is enough for this region to provide the services for private users and to solve applied geodesic problems with high precision. To solve the problem of coordinate transformation in real time mode, it has been offered to use a single stage procedure of coordinate transformation for the field controllers that have the possibility to work with transformation fields. The procedure is based on the application of additionally modeled (ETRS89 — USK-2000) coordination difference onto the (USK-2000 — SK-42) transformation field.
Использование технологии кинематики в реальном времени (RTK) для решения прикладных задач геодезии
Using technology in Real Time Kinematics (RTK) solutions for applications research
Keywords: супутникові технології; референцна станція; пересувний приймач; поправки; трансформація координат; спутниковые технологии; референцных станция; передвижной приемник; поправки; трансформация координат; satellite technology; reference station; mobile receiver; corrections coordinates; transformation of coordinates